Metacercariae of Renifer heterocoelium (Trematoda: Reniferidae) in tadpoles of Rhinella schneideri (Anura: Bufonidae) in Brazil - Hudson Alves Pinto; Alan Lane de Melo (Revista Mexicana de Biodiversidad)
Renifer heterocoelium is a parasite of the oral cavity of Neotropical snakes for which larval stages and the life cycle are still unknown. During studies of parasites of Rhinella schneideri, tadpoles collected in a lake from the municipality of Santa Luzia, Minas Gerais, Brazil, yielded specimens with metacercariae adhered to the external intestinal wall. After morphological characterization, the metacercariae were identified as R. heterocoelium. This is the first record and morphological characterization of metacercariae of R. heterocoelium for Brazil. Key words: Rhinella schneideri, Amphibia, Bufonidae, Renifer heterocoelium, Digenea